2017
DOI: 10.1002/pro.3147
|View full text |Cite
|
Sign up to set email alerts
|

Breaking up and making up: The secret life of the vacuolar H+‐ATPase

Abstract: The vacuolar ATPase (V-ATPase; V 1 V o -ATPase) is a large multisubunit proton pump found in the endomembrane system of all eukaryotic cells where it acidifies the lumen of subcellular organelles including lysosomes, endosomes, the Golgi apparatus, and clathrin-coated vesicles. V-ATPase function is essential for pH and ion homeostasis, protein trafficking, endocytosis, mechanistic target of rapamycin (mTOR), and Notch signaling, as well as hormone secretion and neurotransmitter release. V-ATPase can also be fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
72
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 69 publications
(79 citation statements)
references
References 103 publications
(217 reference statements)
2
72
0
Order By: Relevance
“…S1E-G) (16,(29)(30)(31). Moreover, a comparison of the cryoEM models of the three rotary states of holo V-ATPase (28) with the structures of autoinhibited V1 (32) and Vo (29,31) showed that while V1 is halted in state 2, free Vo adopted state 3 (10) (Supplementary Fig. S1).…”
Section: Role Of Subunit H In V-atpase Assemblymentioning
confidence: 99%
See 2 more Smart Citations
“…S1E-G) (16,(29)(30)(31). Moreover, a comparison of the cryoEM models of the three rotary states of holo V-ATPase (28) with the structures of autoinhibited V1 (32) and Vo (29,31) showed that while V1 is halted in state 2, free Vo adopted state 3 (10) (Supplementary Fig. S1).…”
Section: Role Of Subunit H In V-atpase Assemblymentioning
confidence: 99%
“…S1). From this observation, we hypothesized that the state mismatch together with the large conformational changes of HCT and aNT that accompany enzyme dissociation explain why V1 does not readily bind free Vo under Role of subunit H in V-ATPase assembly physiological conditions in vitro (10,33), a safety-mechanism that likely evolved to prevent spontaneous reassembly in vivo when the disassembled state is required.…”
Section: Role Of Subunit H In V-atpase Assemblymentioning
confidence: 99%
See 1 more Smart Citation
“…In order to accomplish an efficient transfer of 4 ATP hydrolysis energy to c-ring rotation, the rotation of A 3 B 3 headpiece is prevented by three peripheral stalks (Zhang et al, 2008). Each of these stalks is composed by a G/E heterodimer, which anchors the A 3 B 3 headpiece to the membrane through either: i) direct binding to the N-terminal tail of a-subunit, or ii) indirectly through subunit C. In particular, while two of three G/E-stalks are directly bound to a-subunit, the third G/Estalk is bound to subunit C, which itself interacts simultaneously with a-subunit and the second G/E-peripheral stalk (Oot & Wilkens, 2012;Oot et al, 2017;Zhang et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…It is noteworthy that during the disassembly of V 1 -sector from V O -sector, the proteinprotein interactions between a-subunit and G/E-stalks as well as C-subunit and G/E-stalk are destabilized through a yet unknown molecular mechanism (Oot et al, 2017).…”
Section: Introductionmentioning
confidence: 99%